2022
DOI: 10.3389/fmolb.2022.899192
|View full text |Cite
|
Sign up to set email alerts
|

Nascent Glycoproteome Reveals That N-Linked Glycosylation Inhibitor-1 Suppresses Expression of Glycosylated Lysosome-Associated Membrane Protein-2

Abstract: Glycosylation inhibition has great potential in cancer treatment. However, the corresponding cellular response, protein expression and glycosylation changes remain unclear. As a cell-permeable small-molecule inhibitor with reduced cellular toxicity, N-linked glycosylation inhibitor-1 (NGI-1) has become a great approach to regulate glycosylation in mammalian cells. Here for the first time, we applied a nascent proteomic method to investigate the effect of NGI-1 in hepatocellular carcinoma (HCC) cell line. Besid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…NGI-1, a small-molecule inhibitor specifically targeting the OST complex, was initially discovered for its ability to inhibit the flaviviruses [ 80 ]. Recently, NGI-1 has been reported to affect the N- glycopeptide of LAMP2, triggering lysosomal defects and autophagy [ 81 ]. In this study, we observed that NGI-1 can inhibit the glycosylation of LAMPs and rescue the degradation of HIF-1 α caused by ALKBH1 knockdown (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NGI-1, a small-molecule inhibitor specifically targeting the OST complex, was initially discovered for its ability to inhibit the flaviviruses [ 80 ]. Recently, NGI-1 has been reported to affect the N- glycopeptide of LAMP2, triggering lysosomal defects and autophagy [ 81 ]. In this study, we observed that NGI-1 can inhibit the glycosylation of LAMPs and rescue the degradation of HIF-1 α caused by ALKBH1 knockdown (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For these aberrant types of N-glycosylation, reducing the aberrant glycosylation phenotype in tumor cells, starting with the relevant glycosyltransferases, may help restore the original cellular activity [ 126 ]. However, due to the limitation of technical means, it may also affect the normal expression and function of other N-glycosylated proteins [ 127 ].…”
Section: Discussionmentioning
confidence: 99%